The effects of vaccination forecasts and value-based payment on adult immunizations by community pharmacists. Issue 1 (3rd January 2019) - Bacci, Jennifer L.; Hansen, Ryan; Ree, Christina; Reynolds, Marci J.; Stergachis, Andy; Odegard, Peggy S.
Abstract: Background: The prevalence of vaccine-preventable diseases in adults remains a significant public health issue in the United States. The objectives of this demonstration project were to increase the number of influenza, pneumococcal, pertussis, and herpes zoster immunizations administered to adults by community pharmacists, evaluate the percentage of immunizations documented in the state immunization information system (IIS), and design and pilot a value-based payment model. Methods: A one-year prospective, observational demonstration project was conducted in 70 community pharmacies in western Washington State from September 1, 2016 to August 31, 2017. An immunization interface was integrated into workflow at each pharmacy to enable "forecasting" of and proactive recommendation to patients about their vaccine needs and documentation of vaccines administered in the state IIS. Categorical value-based payment models were developed and implemented in a subgroup of 12 community pharmacies from March 1 to November 30, 2017. The change in the number of immunizations administered in comparison to the baseline period and the percentage of immunizations documented in the state IIS during the demonstration period were analyzed using descriptive statistics. Results: There was a 15% total increase in the collective number of influenza, pneumococcal, pertussis, and herpes zoster vaccines administered in the demonstration year in the 70 pharmacies, due to increases in influenza and pertussis vaccinations. Eighty-three percent of the vaccines administered were documented in the state IIS. Pneumococcal, pertussis, and herpes zoster performance appeared to be unaffected by the value-based payment models while influenza performance improved across the 12 pilot pharmacies. Conclusions: This work demonstrated that community pharmacists contribute to improving adult immunizations through vaccine "forecasting" and proactive recommendation. Meaningful quality measures with both positive and negative incentives could further drive adoption of best immunization practices. Further implementation and outcomes research is needed to fully examine the impact and scalability of these strategies.